AlCrTiXN coating for cutting titanium alloy and production process
Through the AlCrTiXN gradient coating process, the problems of insufficient tool wear resistance and easy oxidation in titanium alloy cutting processing are solved, and a coating that is strongly combined with titanium alloy parts is realized, which significantly improves cutting performance and stability.
Patent Information
- Application Number
- CN202510008313.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-03
AI Technical Summary
During the cutting process, titanium alloys have difficulty in processing due to their high strength, low thermal conductivity, high chemical activity and low elastic modulus. The existing coating tools have problems such as insufficient wear resistance, easy oxidation and easy shedding.
The AlCrTiXN gradient coating process is adopted to form a gradient coating that is strongly combined with the cemented carbide tool matrix through steps such as soft sand spraying, ultrasonic treatment and vacuum drying, which improves its chemical stability, anti-adhesion performance and wear resistance.
The bonding force between titanium alloy cutting tools and titanium alloy parts is significantly improved, the chemical stability, anti-adhesion and wear resistance of the coating are enhanced, and the problems of easy oxidation and easy falloff of existing tools are solved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy coatings and relates to an AlCrTiXN coating for cutting titanium alloys and a production process. Background Art
[0002] Titanium alloy is a high-strength and lightweight material with excellent heat resistance and corrosion resistance. It is widely used in many fields such as aviation, aerospace, automobile, chemistry and biology. Especially in the field of aerospace, the proportion of titanium alloy used is increasing year by year. Using titanium alloy to manufacture aircraft parts can not only extend the service life of the aircraft, but also reduce its weight, reduce fuel consumption, and significantly improve flight performance.
[0003] However, with the advancement of high-speed cutting technology and the increase in demand for thin-walled integral parts, the difficulty of titanium alloy processing has become more prominent. Its high strength, low thermal conductivity, high chemical activity and low elastic modulus are the key factors that make titanium alloy cutting difficult. At present, although there are coated tools on the market for cutting titanium alloys, these tools still face problems such as insufficient wear resistance, easy oxidation and easy shedding. With the rapid development of the manufacturing industry, the application of titanium alloys will increase day by day, and the requirements for quality and precision will continue to increase. Therefore, choosing more suitable titanium alloy cutting tools, improving the level of industrialized production in the industry, and reducing the manufacturing cost of titanium alloys are of far-reaching significance to the sustainable development of mechanical processing and the improvement of the overall level of the manufacturing industry.
[0004] When a carbide tool for cutting titanium alloy is exposed to the atmosphere or aqueous solution, a dense oxide film will form on the surface. This film is very strong. The oxide film will be thicker on the surface of parts that have been cast and heat treated. Once the oxide film is damaged by mechanical damage, it can quickly repair itself, so it is difficult to remove. After the oxide film on the surface of the carbide tool is removed by inorganic acid etching, a new oxide film will immediately form on the fresh surface once it comes into contact with air, water or aqueous solution. In order to obtain good coating adhesion, the oxide film on the surface of the carbide tool must first be thoroughly removed, and secondly, the activity of the alloy surface must be maintained so that it is stable before the deposition of the coating metal. Therefore, the pretreatment method of the carbide tool will directly affect the bonding between the subsequent metal coating and the carbide tool substrate. Summary of the invention
[0005] The purpose of the present invention is to provide an AlCrTiXN coating and a production process for cutting titanium alloys. The gradient coating prepared by the present invention exhibits stronger bonding with a cemented carbide tool substrate and has excellent chemical stability, anti-adhesion performance and wear resistance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0008] 1) Degreasing, degreasing and cleaning the tool, blasting soft sand, immersing in a mixed solution under an inert atmosphere, ultrasonically treating the tool, taking it out, cleaning it and vacuum drying it to obtain a pretreated cemented carbide tool;
[0009] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, and the ALCr composite target arc power supply and the TiZr alloy target power supply are turned on for deposition treatment;
[0010] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 350-380°C for 15-30 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature to obtain a gradient coating.
[0011] As a preferred technical solution of the present invention, in step 1), the tool is a milling cutter specially used for titanium alloy cutting; the soft sand blasting is sand blasting at a pressure of 0.16-0.20MPa for 24-30min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasonic treatment at a temperature of 40-50°C and a power of 400-500W for 30-40s; and the vacuum drying is vacuum drying at a temperature of 80°C to constant weight.
[0012] As a preferred technical solution of the present invention, in step 1), the mixed solution is composed of hydrochloric acid, oxalic acid, auxiliary agent and solvent in a mass ratio of 40-42:25-28:6.2-7.0:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.0-2.3:1.4-1.5; the preparation of the benzenethiol derivative comprises mixing protocatechuic aldehyde and anhydrous ethanol, adding m-aminothiophenol, stirring at a temperature of 50-60°C for 4-5h, and centrifuging to obtain the product; the mass ratio of protocatechuic aldehyde, m-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0013] As a preferred technical solution of the present invention, in step 2), the parameters of the ALCr composite target arc power supply are 90-120A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2-3A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 0.8-1.2Pa, and the bias voltage is 60-100V.
[0014] As a preferred technical solution of the present invention, the thickness of the gradient coating is 120-160nm, and the atomic percentage of each element in the gradient coating is: Al is 16.2-16.6at.%, Cr is 9.4-10at.%, Zr is 18.5-18.8at.%, Ti is 10.66-10.68at.%, and the rest is N element.
[0015] Beneficial effects of the present invention:
[0016] (1) The gradient coating prepared by the present invention exhibits stronger bonding strength with the cemented carbide tool substrate and has excellent chemical stability, anti-adhesion performance and wear resistance.
[0017] (2) The present invention can improve the etching effect of oxalic acid through hydrochloric acid, and sodium dodecyl sulfate can reduce its surface tension, improve its wettability and permeability, and promote hydrochloric acid and oxalic acid to better contact and dissolve the surface oxide layer; the benzenethiol derivative contains thiol and imine structures and forms a stable complex with metal ions, which prevents the metal ions from re-depositing on the surface during the treatment process and improves the removal effect of the oxide layer. It also contains a catechol structure with antioxidant properties, which can prevent the treated surface from being oxidized again and maintain the activity of the surface. The synergistic effect of the imine structure, thiol group and catechol structure can enhance the adsorption of the inhibitor and the metal, and can also be adapted to the adsorption of various metals, reduce their oxidative corrosion, and provide protection for titanium alloy metals. DETAILED DESCRIPTION
[0018] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0019] Example 1
[0020] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0021] 1) Degreasing, degreasing, and cleaning the hard tungsten-cobalt alloy tool YG8, blasting soft sand, immersing it in a mixed solution under an inert atmosphere, ultrasonically treating it, filtering it, cleaning it, and vacuum drying it at 80° C. to constant weight to obtain a pretreated hard alloy tool;
[0022] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the ALCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment;
[0023] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 350°C for 15 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
[0024] In step 1), the soft sand blasting is sand blasting at a pressure of 0.16MPa for 24min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasound at a temperature of 40°C and a power of 400W for 30s; the mixed solution is composed of hydrochloric acid, oxalic acid, an auxiliary agent and a solvent in a mass ratio of 40:25:6.2:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.0:1.4; the preparation of the benzenethiol derivative includes mixing protocatechuic aldehyde and anhydrous ethanol, adding meta-aminothiophenol, stirring at a temperature of 50°C for 4h, and centrifuging to obtain the obtained product; the mass ratio of protocatechuic aldehyde, meta-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0025] In step 2), the parameters of the ALCr composite target arc power supply are 90A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 0.8Pa, and the bias voltage is 80V.
[0026] The thickness of the gradient coating is 120 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.2 at.%, Cr is 9.4 at.%, Zr is 18.5 at.%, and Ti is 10.66 at.%.
[0027] Example 2
[0028] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0029] 1) Degreasing, degreasing, and cleaning the hard tungsten-cobalt alloy tool YG8, blasting soft sand, immersing it in a mixed solution under an inert atmosphere, ultrasonically treating it, taking it out, cleaning it, and vacuum drying it at 80° C. to constant weight to obtain a pretreated hard alloy tool;
[0030] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the ALCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment;
[0031] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 358°C for 19 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
[0032] In step 1), the soft sand blasting is sand blasting at a pressure of 0.17MPa for 26min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasound at a temperature of 42°C and a power of 425W for 32s; the mixed solution is composed of hydrochloric acid, oxalic acid, an auxiliary agent and a solvent in a mass ratio of 40.5:25.8:6.4:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.1:1.42; the preparation of the benzenethiol derivative comprises mixing protocatechuic aldehyde and anhydrous ethanol, adding m-aminothiophenol, stirring at a temperature of 52°C for 4.2h, and centrifuging to obtain the product; the mass ratio of protocatechuic aldehyde, m-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0033] In step 2), the parameters of the AlCr composite target arc power supply are 98A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2.2A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 0.9Pa, and the bias voltage is 90V.
[0034] The thickness of the gradient coating is 130 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.3 at.%, Cr is 9.6 at.%, Zr is 18.57 at.%, Ti is 10.665 at.%, and the rest is N element.
[0035] Example 3
[0036] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0037] 1) Degreasing, degreasing, and cleaning the hard tungsten-cobalt alloy tool YG8, blasting soft sand, immersing it in a mixed solution under an inert atmosphere, ultrasonically treating it, taking it out, cleaning it, and vacuum drying it at 80° C. to constant weight to obtain a pretreated hard alloy tool;
[0038] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the AlCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment;
[0039] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 365°C for 22 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
[0040] In step 1), the soft sand blasting is sand blasting at a pressure of 0.18MPa for 27min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasound at a temperature of 45°C and a power of 450W for 35s; the mixed solution is composed of hydrochloric acid, oxalic acid, an auxiliary agent and a solvent in a mass ratio of 41:26.5:6.6:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.15:1.45; the preparation of the benzenethiol derivative includes mixing protocatechuic aldehyde and anhydrous ethanol, adding m-aminothiophenol, stirring at a temperature of 55°C for 4.5h, and centrifuging to obtain the product; the mass ratio of protocatechuic aldehyde, m-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0041] In step 2), the parameters of the AlCr composite target arc power supply are 105A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2.5A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 1Pa, and the bias voltage is 100V.
[0042] The thickness of the gradient coating is 140 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.4 at.%, Cr is 9.7 at.%, Zr is 18.65 at.%, Ti is 10.67 at.%, and the rest is N element.
[0043] Example 4
[0044] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0045] 1) Degreasing, degreasing, and cleaning the hard tungsten-cobalt alloy tool YG8, blasting soft sand, immersing it in a mixed solution under an inert atmosphere, ultrasonically treating it, taking it out, cleaning it, and vacuum drying it at 80° C. to constant weight to obtain a pretreated hard alloy tool;
[0046] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the AlCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment;
[0047] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 372°C for 26 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
[0048] In step 1), the soft sand blasting is sand blasting at a pressure of 0.19MPa for 28min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasound at a temperature of 48°C and a power of 470W for 38s; the mixed solution is composed of hydrochloric acid, oxalic acid, an auxiliary agent and a solvent in a mass ratio of 41.5:27:6.8:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.22:1.48; the preparation of the benzenethiol derivative comprises mixing protocatechuic aldehyde and anhydrous ethanol, adding m-aminothiophenol, stirring at a temperature of 58°C for 4.8h, and centrifuging to obtain the product; the mass ratio of protocatechuic aldehyde, m-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0049] In step 2), the parameters of the AlCr composite target arc power supply are 102A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2.8A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 1.1Pa, and the bias voltage is 90V.
[0050] The thickness of the gradient coating is 150 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.5 at.%, Cr is 9.8 at.%, Zr is 18.7 at.%, Ti is 10.675 at.%, and the rest is N element.
[0051] Example 5
[0052] A production process for cutting AlCrTiXN coating for titanium alloy TC4 comprises the following steps:
[0053] 1) Degreasing, degreasing, and cleaning the hard tungsten-cobalt alloy tool YG8, blasting soft sand, immersing it in a mixed solution under an inert atmosphere, ultrasonically treating it, taking it out, cleaning it, and vacuum drying it at 80° C. to constant weight to obtain a pretreated hard alloy tool;
[0054] 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the AlCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment;
[0055] 3) Turn off all targets, bias power supply and gas source, keep the temperature at 380°C for 30 minutes, then cool down to below 100°C with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
[0056] In step 1), the soft sand blasting is sand blasting at a pressure of 0.20MPa for 30min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasound at a temperature of 50°C and a power of 500W for 40s; the mixed solution is composed of hydrochloric acid, oxalic acid, an auxiliary agent and a solvent in a mass ratio of 42:28:7.0:1000; the solvent is a 20wt% ethanol aqueous solution; the auxiliary agent is a mixture of a thiophenol derivative and sodium dodecyl sulfate in a mass ratio of 2.3:1.5; the preparation of the benzenethiol derivative includes mixing protocatechuic aldehyde and anhydrous ethanol, adding meta-aminothiophenol, stirring at a temperature of 60°C for 5h, and centrifuging to obtain the obtained product; the mass ratio of protocatechuic aldehyde, meta-aminothiophenol and anhydrous ethanol is 1.8:2.5:20.
[0057] In step 2), the parameters of the AlCr composite target arc power supply are 120A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 3A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 1.2Pa, and the bias voltage is 100V.
[0058] The thickness of the gradient coating is 160 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.6 at.%, Cr is 10 at.%, Zr is 18.8 at.%, Ti is 10.68 at.%, and the rest is N element.
[0059] Comparative Example 1
[0060] Compared with Example 3, Comparative Example 1 is different in that sodium lauryl sulfate is not used, and the remaining components, preparation steps and parameters are the same.
[0061] Comparative Example 2
[0062] Compared with Example 3, the difference in Comparative Example 2 is that aniline replaces m-aminothiophenol, and the other components, preparation steps and parameters are the same.
[0063] Comparative Example 3
[0064] Compared with Example 3, the difference in Comparative Example 3 is that thiophenol replaces m-aminothiophenol, and the other components, preparation steps and parameters are the same.
[0065] Comparative Example 4
[0066] Compared with Example 3, Comparative Example 4 is different in that benzaldehyde replaces protocatechuic aldehyde, and the other components, preparation steps and parameters are the same.
[0067] Comparative Example 5
[0068] Compared with Example 3, Comparative Example 5 is different in that no benzenethiol derivative is used, and the remaining components, preparation steps and parameters are the same.
[0069] The tool coatings prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following performance tests, respectively. The test results are shown in Table 1.
[0070] Plating adhesion test: Use the file method and observe the coating morphology; according to GB / T5270-2005;
[0071] Hardness test: Hardness test of the coating according to ASTM-E-384;
[0072] Table 1
[0073] Coating bonding strength Hardness (HV) Example 1 The coating bonding strength is qualified 3759 Example 2 The coating bonding strength is qualified 3763 Example 3 The coating bonding strength is qualified 3712 Example 4 The coating bonding strength is qualified 3766 Example 5 The coating bonding strength is qualified 3698 Comparative Example 1 Edge plating is peeling off 3267 Comparative Example 2 The coating is cracked and peeled off 3361 Comparative Example 3 The coating is cracked and peeled off 3106 Comparative Example 4 Edge plating is peeling off 3298 Comparative Example 5 The coating is cracked and peeled off seriously 3009
[0074] From the test results in Table 1, it can be seen that compared with comparative examples 1-5, the coatings prepared in embodiments 1-5 have excellent bonding strength with the cemented carbide tool substrate and have significant hardness performance.
[0075] The present invention can improve the etching effect of hydrofluoric acid by hydrochloric acid, and sodium dodecyl sulfate can reduce its surface tension, improve its wettability and permeability, and promote hydrofluoric acid to better contact and dissolve the oxide layer on the surface; the benzenethiol derivative contains a thiol group and an imine structure and forms a stable complex with metal ions, which prevents the metal ions from being re-deposited on the surface during the treatment process and improves the removal effect of the oxide layer; it also contains a catechol structure with antioxidant properties, which can prevent the treated surface from being oxidized again and maintain the activity of the surface; the adsorption effect of the inhibitor and the metal can be enhanced through the synergistic effect of the imine structure, the thiol group and the catechol structure, and can also be adapted to the adsorption of various metals, reduce their oxidative corrosion, and provide a protective effect on titanium alloy metals.
[0076] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A production process for AlCrTiXN coating for cutting titanium alloy TC4, characterized in that: The production process comprises the following steps: 1) Degreasing, degreasing and cleaning the cemented carbide tool, blasting soft sand, immersing in a mixed solution under an inert atmosphere, ultrasonically treating the tool, taking it out, cleaning it and vacuum drying it to obtain a pretreated cemented carbide tool; 2) In an inert atmosphere, the pretreated carbide tool is placed in a vacuum chamber, the nitrogen gas source is turned on, and the ALCr composite target arc power supply and the TiZr alloy target power supply are turned on simultaneously for deposition treatment; 3) Turn off all targets, bias power supply and gas source, perform heat preservation treatment and then cool down with the furnace, take out the tool, cool at room temperature, and obtain a gradient coating.
2. The production process of the AlCrTiXN coating for cutting titanium alloy TC4 according to claim 1, characterized in that: In step 1), the cemented carbide tool is a titanium alloy special milling cutter; the soft sand blasting is sand blasting at a pressure of 0.16-0.20MPa for 24-30min; the inert atmosphere is an Ar gas atmosphere; the ultrasonic treatment is ultrasonic treatment at a temperature of 40-50°C and a power of 400-500W for 30-40s; and the vacuum drying is vacuum drying at a temperature of 80°C to constant weight.
3. The production process of the AlCrTiXN coating for cutting titanium alloy TC4 according to claim 1, characterized in that: In step 1), the mixed solution is composed of hydrochloric acid, oxalic acid, auxiliary agent and solvent in a mass ratio of 40-42:25-28:6.2-7.0:1000.
4. The production process of the AlCrTiXN coating for cutting titanium alloy TC4 according to claim 1, characterized in that: In step 2), the parameters of the ALCr composite target arc power supply are 90-120A current, the parameters of the TiZr alloy target power supply are 150A initial current and reduced at a rate of 2-3A / min, and the tool substrate is treated for 150min; the working gas pressure in the vacuum chamber is 0.8-1.2Pa, and the bias voltage is 60-100V.
5. The production process of the AlCrTiXN coating for cutting titanium alloy TC4 according to claim 1, characterized in that: In step 3), the thickness of the gradient coating is 120-160 nm, and the atomic percentage of each element in the gradient coating is: Al is 16.2-16.6 at.%, Cr is 9.4-10 at.%, Zr is 18.5-18.8 at.%, Ti is 10.66-10.68 at.%, and the rest is N element.
6. The production process of the AlCrTiXN coating for cutting titanium alloy according to claim 1, characterized in that: In step 3), the heat preservation treatment is to keep the temperature at 350-380°C for 15-30 minutes, and the furnace cooling is to cool the temperature to below 100°C.
Citation Information
Patent Citations
Conductive corrosion-resistant titanium metal bipolar plate for fuel cell and preparation method
CN111342073A
Novel gas diffusion layer for fuel cell as well as preparation method and application of novel gas diffusion layer
CN114267850A
Fuel cell bipolar plate based on Ti coating surface modification and preparation method thereof
CN114792819A
Co-deposition of conductive material at the diffusion media / plate interface
US20110189580A1